In‐field and out‐of‐field microdosimetric characterisation of a 62 MeV proton beam at CATANA. Issue 8 (23rd June 2021) - James, Benjamin; Tran, Linh T.; Bolst, David; Prokopovich, Dale A.; Lerch, Michael; Petasecca, Marco; Guatelli, Susanna; Povoli, Marco; Kok, Angela; Petringa, Giada; Cirrone, Giuseppe A.P.; Jackson, Michael; et al.
Abstract : Purpose: A 5 and 10 μm thin silicon on insulator (SOI) 3D mushroom microdosimeter was used to characterize both the in‐field and out‐of‐field of a 62 MeV proton beam. Methods: The SOI mushroom microdosimeter consisted of an array of cylindrical sensitive volumes (SVs), developed by the Centre for Medical Radiation Physics, University of Wollongong, was irradiated with 62 MeV protons at the CATANA (Centro di AdroTerapia Applicazioni Nucleari Avanzate) facility in Catania, Italy, a facility dedicated to the radiation treatment of ocular melanomas. Dose mean lineal energy, ( y D ¯ ), values were obtained at various depths in PMMA along a pristine and spread out Bragg peak (SOBP). The measured microdosimetric spectra at each position were then used as inputs into the modified Microdosimetric Kinetic Model (MKM) to derive the RBE for absorbed dose in a middle of the SOBP 2Gy (RBED ). Microdosimetric spectra were obtained with both the 5 and 10 μm 3D SOI microdosimeters, with a focus on the distal part of the BP. The in‐field and out‐of‐field measurement configurations along the Bragg curve were modeled in Geant4 for comparison with experimental results. Lateral out‐of‐field measurements were performed to study secondary particles' contribution to normal tissue's dose, up to 12 mm from the edge of the beam field, and quality factor and dose equivalent results were obtained. Results: Comparison between experimental and simulation results showed good agreement between one another for both the pristine and SOBP beams in terms of y D ¯ and RBED. Though a small discrepancy between experiment and simulation was seen at the entrance of the Bragg curve, where experimental results were slightly lower than Geant4. The dose equivalent value measured 12 mm from the edge of the target volume was 1.27 ± 0.15 mSv/Gy with a Q ¯ value of 2.52 ± 0.30, both of which agree within uncertainty with Geant4 simulation. Conclusions: These results demonstrate that SOI microdosimeters are an effective tool to predict RBED in‐field as well as dose equivalent monitoring out‐of‐field to provide insight to probability of second cancer generation.